2000
DOI: 10.1002/(sici)1097-4644(2000)77:34+<35::aid-jcb8>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Utilization ofK-ras mutations identified in stool DNA for the early detection of colorectal cancer

Abstract: Colorectal cancer is one of the most common malignancies in the western world. About 60,000 Americans die of colorectal cancer each year. The annual incidence rate in Israel is 40 per 100,000 persons, namely a total of 2,000 new cases each year. An important step in the progression of colorectal cancer includes induction of activating mutations in the proto-oncogene K-ras. The mutations in K-ras appear early during tumorigenesis, at the intermediate adenoma stage, and thus can be used as a biomarker for early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Subsequent reports also involved interrogation of single genetic targets. [13][14][15][16][17] More recently, assays with multiple markers have been developed 18,19 to yield increased assay sensitivity in light of the genetic heterogeneity of sporadic CRC cases. Furthermore, an assay for long DNA recovered from stool has been developed and shown to be associated with CRC with high specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent reports also involved interrogation of single genetic targets. [13][14][15][16][17] More recently, assays with multiple markers have been developed 18,19 to yield increased assay sensitivity in light of the genetic heterogeneity of sporadic CRC cases. Furthermore, an assay for long DNA recovered from stool has been developed and shown to be associated with CRC with high specificity.…”
Section: Discussionmentioning
confidence: 99%
“…An important step in the progression of colorectal cancer is the induction of activating mutations in KRAS proto-oncogene, GTPase (KRAS). Mutations in KRAS appear in the intermediate adenoma stage, early during tumorigenesis, and it is thus possible to use them as a biomarker for early detection of ~40% of colorectal tumors (8).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the majority of studies have shown that mutations are found more frequently in tissues than in stools. 13,29,30,35,36 In this study, four patients (nos. 2, 17, 20, and 26) exhibiting mutant electrophoresis patterns in both stool samples and cancer tissues were found by direct sequencing to carry K-ras mutations in their cancer tissues but not in their stool samples, whereas clone sequencing confirmed the K-ras mutations in their stool samples, showing that the proportions of mutant K-ras were 9, 12, 15, and 13%, respectively, which demonstrated the lower abundance of K-ras mutations in stool samples compared with that in cancer tissues.…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6] Based on the good clinical compliance and the findings of several research groups that revealed K-ras mutations in stools consistent with the K-ras status in matching Chip-based detection of stool K-ras mutation H Zhang et al tumor tissues, [28][29][30] mutated DNA in stools has become the latest target of several detection methods. [8][9][10] Although stoolbased DNA detection could report CRC tissue K-ras genotypes faithfully, severe difficulties because of complicated procedures and low sensitivity have hampered further progress in using stool samples to detect K-ras mutations and preventatively screen for CRC.…”
Section: Discussionmentioning
confidence: 99%